Assessing disaster vulnerability in an informal settlement of Cape Town, South Africa, through the MOVE framework - Kunguma, Olivia; Awah, Lum Sonita; Petersen, Ilona; Lunga, Wilfred (Frontiers in Built Environment, 2025)
IntroductionInformal settlements in South Africa remain highly exposed to disasters despite continued disaster risk reduction (DRR) interventions. Khayelitsha—particularly the Barney Molokwane (BM) Section—is among Cape Town’s most flood- and fire-prone areas. Understanding vulnerability in such contexts requires frameworks capable of unpacking the interaction of exposure, susceptibility, and resilience. This study applies the Methods for the Improvement of Vulnerability Assessment in Europe (MOVE) framework to assess the drivers of vulnerability in BM Section and situates findings within comparable evidence from Africa, Asia, and Latin America.MethodsA mixed-methods design was employed, integrating household surveys with 125 randomly selected residents, transect walks, and systematic field observations. The MOVE framework structured the assessment across three components—exposure, susceptibility, and resilience. Quantitative and qualitative data were triangulated to capture settlement conditions, socio-economic factors, governance interactions, and everyday coping strategies.ResultsVulnerability in BM Section is shaped by intersecting socio-economic, environmental, and institutional factors. Key drivers include inadequate housing, overcrowding, unemployment, poor sanitation, and infrastructure deficits. Exposure is intensified by wetland encroachment and the dismantling of protective berms. Hazardous coping practices—such as illegal electricity connections and resistance to re-blocking—reflect governance shortcomings, mistrust, and limited access to basic services rather than community unwillingness. Comparative literature shows that while wetland encroachment is context-specific, poverty and weak institutional engagement are widespread determinants of urban informal settlement vulnerability.DiscussionThe MOVE framework effectively illuminates multidimensional vulnerability but captures cultural factors and informal social safety nets less comprehensively. Findings point to the need for participatory governance approaches, including co-developed early warning systems, community-driven drainage solutions, and livelihood support mechanisms. The study demonstrates the value of structured vulnerability assessment for informing flood-risk management and climate adaptation planning in informal settlements, contributing to progress toward SDG 11: Sustainable Cities and Communities.